Metachromatic leucodystrophy: review of 38 cases. Issue 3 (March 1982) - MacFaul, R; Cavanagh, N; Lake, B D; Stephens, R; Whitfield, A E
Abstract : Clinical and laboratory features of 38 children suffering from metachromatic leucodystrophy (MLD) are reported. Twenty-four children with the late infantile form of MLD presented between ages 6 and 25 (mean 17) months with a delay or deterioration in walking, followed by a general loss of abilities. There was severe handicap by age 3 years and death occurred between 5 months and 8 years after presentation. Neurological signs at the time of diagnosis were varied. Motor nerve conduction velocity was slowed in the 18 children tested. The disease became evident at a later age in 14 children. One boy presented at 13 years, while in the remainder there appeared to be two clinical patterns of the disease which could be termed (1) early juvenile or intermediate and (2) juvenile MLD. In 7 children with early juvenile or intermediate MLD a gait disorder developed between ages 4 and 6 (mean 5) years. This was accompanied in 4 children, and followed between 8 and 26 months later in the remaining 3, by loss of other abilities. Neurological signs were varied. Motor nerve conduction velocity was slowed in 2 of the 5 patients tested. Six children with juvenile MLD presented between ages 6 and 10 years with educational or behavioural difficulties. Motor disorders arose from 6 months to 4 years later. Neurological signs at the time of diagnosis, although mixed, were predominantly extrapyramidal and motor nerve conduction velocity was slowed in 2 of the 3 children tested. In the early juvenile form of MLD, progression of the disease was slower than in the late infantile form and death occurred between 31/2 and 18 years after presentation. Only one-third of patients had fits and these tended to be a late feature.